Blue-and-yellow Macaw (Ara ararauna; Linnaeus, 1758) and its novel and major food, Terminalia catappa L. seeds, in an urban area in Central Brazil - J. Ragusa-Netto (Brazilian Journal of Biology, 2025)
Abstract Blue-and-yellow Macaws in Três Lagoas City (State of Mato Grosso do Sul, Brazil) have utilized Terminalia catappa seeds increasingly, after rarely eating this resource fifteen years ago. Consequently, to improve our understanding of the importance of this novel food in urban areas (center and peri-urban), I once again documented the feeding habits and diet breadth of Blue-and-yellow Macaws in Três Lagoas City and analyzed their responses to resource availability. Blue-and-yellow Macaws foraged on 16 plant species (10 native and 6 exotic), with T. catappa dominating their diet (43.6%), particularly in sites in the city center (up to 81%). Overall, exotic items comprise 50.9% of the Blue-and-Yellow Macaw’s current diet, compared to only 5.4% fifteen years before (from April 2007 to March 2008). Due to the extensive consumption of T. catappa seeds, macaws generally exhibited low diet breadth, especially in the city center. In contrast, in the peri-urban areas, the diet was varied, exhibiting intermediate values of diet breadth. Paralleling the increased presence of exotic species in the Blue-and-yellow Macaw’s diet, the native food resources, especially Cerrado fruits, have been reduced by the expansion of urban areas and eucalyptus plantations. As a result, in just a few years, T. catappa has become the primary food for the Blue-and-yellow Macaw, displaying extreme dietary flexibility to survive in a rapidly changing urban environment. To mitigate such impacts, it is suggested that native species, which once dominated the macaw diet, be used for afforestation throughout the city to encourage a more similar species-rich diet that this macaw eats in the Cerrado. The extensive use of the urban area by Blue-and-yellow Macaws underscores the need for management practices to improve their population growth, as they, unfortunately, are declining along with the Cerrado.